It Happened in Ghana. A Historical Romance 1824-1971 - Smith, Noel (Teacher) (Book collections on Project MUSE., 2007)
It Happened in Ghana carries a positive message. Conceived as a literary work, it demonstrates that racial prejudice based on skin colour is not a pervasive and unalterable human condition. The principal characters who are both black and white are embroiled in various encounters, notably wars, slave trade, colonialism and post colonial reconstruction. Regardless of their skin colour and cultural differences, they make friends or fall in love secretly during these encounters. When they are forced to part company by the cessation of hostilities or whatever brought them together, they serve in various capacities in new locations outside their original places of domicile. They are accepted or integrated into existing social structures because of the warmth oftheir personalities and the manner in which they are able to adjust themselves to the pressures and challenges of new environments. Changes in the circumstances of the principal characters or their descendants enable them not only to restore broken relationships but also to identify themselves with the cause of freedom and justice or to reconnect in various ways with the development aspirations of Ghana where it all started.